The Application Of Financial Accounting Standards (Sak-Emkm) In The Preparation Of Financial Statements At Berkah Cosmetics Store - Rifah Aulia; Neri Susanti; Ramadan Subhi (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2026)
This study aims to analyze the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM) in the preparation of financial statements at Berkah Kosmetik Store. Micro, Small, and Medium Enterprises (MSMEs) play a significant role in Indonesia’s economy by creating employment opportunities and reducing unemployment. However, many MSMEs still face challenges in managing their financial records properly and in accordance with applicable accounting standards. This research is motivated by the importance of standardized financial reporting to ensure transparency, accountability, and effective decision-making for business sustainability. This study uses a qualitative descriptive approach. Data were collected through interviews, observations, and documentation to obtain an in-depth understanding of financial recording practices at Berkah Kosmetik Store. The results show that the store has not fully implemented SAK-EMKM in preparing its financial statements. Financial recording is still limited to simple bookkeeping of income and expenses, without comprehensive financial statements such as balance sheets, income statements, and notes to financial statements in accordance with SAK-EMKM. The main obstacles identified include limited understanding of accounting standards, lack of accounting skills, and the perception that accounting is complicated and difficult to apply. Therefore, it is recommended that business owners receive training and assistance in implementing SAK-EMKM to improve the quality of financial reporting. Proper implementation of SAK-EMKM is expected to support better financial management, enhance business performance, and ensure the sustainability of Berkah Kosmetik Store.